The Role of Classroom Management in Early Childhood Learning Concrentration - Siti Nur Alimah; Maria Qoriah; Imam Wahyono; Ria Octa Viana (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Learning concentration is an essential aspect of early childhood education because it influences children's ability to receive, process, and respond to learning experiences. However, many early childhood education institutions still face challenges related to classroom physical conditions, such as limited space, classroom layout, lighting, and ventilation, which may affect children's concentration during learning activities. This research is based on the urgency of learning concentration in early childhood, which is influenced by the physical management of classrooms. The main objective is to analyze the influence of classroom management on student learning concentration. The approach used is qualitative through a case study, with children aged 4–6 years at Bustanul Falah Kindergarten for one month. Data were collected through observation, interviews, and documentation. The results indicate that classroom layout, lighting, ventilation, and cleanliness support children's learning concentration despite limited classroom space. Teachers addressed this challenge through flexible seating arrangements and adjustments to classroom layout based on learning activities. It can be concluded that optimal physical classroom management helps create a learning environment that supports children's concentration. Ultimately, strategic management of the physical classroom environment is essential for fostering a supportive atmosphere that enhances children's cognitive focus.